The H-Index as a Quantitative Indicator of the Relative Impact of Human Diseases - McIntyre, K. Marie; Hawkes, Iain; Waret-Szkuta, Agnès; Morand, Serge; Baylis, Matthew (PLOS ONE, 2011)
Assessment of the relative impact of diseases and pathogens is important for agencies and other organizations charged with providing disease surveillance, management and control. It also helps funders of disease-related research to identify the most important areas for investment. Decisions as to which pathogens or diseases to target are often made using complex risk assessment approaches; however, these usually involve evaluating a large number of hazards as it is rarely feasible to conduct an in-depth appraisal of each. Here we propose the use of the H-index (or Hirsch index) as an alternative rapid, repeatable and objective means of assessing pathogen impact. H-index scores for 1,414 human pathogens were obtained from the Institute for Scientific Information's Web of Science (WOS) in July/August 2010. Scores were compared for zoonotic/non-zoonotic, and emerging/non-emerging pathogens, and across taxonomic groups. H-indices for a subset of pathogens were compared with Disability Adjusted Life Year (DALY) estimates for the diseases they cause. H-indices ranged from 0 to 456, with a median of 11. Emerging pathogens had higher H-indices than non-emerging pathogens. Zoonotic pathogens tended to have higher H-indices than human-only pathogens, although the opposite was observed for viruses. There was a significant correlation between the DALY of a disease and the H-index of the pathogen(s) that cause it. Therefore, scientific interest, as measured by the H-index, appears to be a reflection of the true impact of pathogens. The H-index method can be utilized to set up an objective, repeatable and readily automated system for assessing pathogen or disease impact.